IMPLEMENTASI PERATURAN BUPATI LEBAK NOMOR 26 TAHUN 2016 TENTANG PENYELENGARAAN KESEHATAN IBU DAN BAYI DALAM PROGRAM UNDANG, JEMPUT, ANTAR SELAMAT (UJAS) DI KECAMATAN CIJAKU KABUPATEN LEBAK - Tardi Setiabudi; Ipah Ema Jumiati; Riswanda Riswanda (http://jurnal.untirta.ac.id/index.php/JIPAGS, 2021)
In 2015, Lebak Regency was the highest contributor to infant mortality and maternal mortality in Banten Province. Researchers want to know how the implementation of the UJAS Program goes according to the Lebak Regent Regulation number 26 of 2016. In this study, researchers used a case study qualitative approach to find out in-depth about the UJAS Program. The theory used by researchers is Edward III (1980), which is about the implementation of public policy. In the process and activities of collecting data in detail, researchers conducted observations, interviews, and triangulation. The community has not yet known about the UJAS program, especially potential program beneficiaries and program beneficiaries, especially from the section on how to use the Program. Not only that, there are still facilities and infrastructure that are not in accordance with the conditions, for example the vehicles for picking up patients are not in accordance with road conditions, there is no special budget to meet the needs of the program and there is no organizational structure so there is no clarity of the UJAS program implementers. Implementers Need to socialize the UJAS Program again so that it can be better known and understood by the wider community. Then allocate a special budget to meet the needs of the UJAS Program, and make the UJAS Program Organizational Structure so that there is clarity on the implementer.